2012
DOI: 10.2478/s11532-012-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of calcium carbonates used in wet flue gas desulphurization processes

Abstract: Abstract:© Versita Sp. z o.o. Keywords: Calcium carbonate reactivity • Wet desulphurization • Absorption capacity • Calcium carbonate precipitate • Slurry concentrationThis paper presents an experimental characterization of two sources of calcium carbonate, limestone and calcium carbonate precipitate (CCP) used in wet flue gas desulphurization processes. Characterization of the two carbonate sources was carried out by chemical analysis, IR spectra, thermal behavior, particle size distribution for CCP, BET sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…It can be assumed that small particles completely reacted at this time and the size of the large particles is decisive. On the other hand, there is only a slight correlation between the reaction rate and the specifi c surface area of the samples, which is in accordance with the published data (Ahlbeck et al, 1993;Ahlbeck et al, 1995;Ukawa et al, 1993;Wallin and Bjerle, 1989;Dragan and Ozunu, 2012;Claudio A. Carleti G., 2015). Good correlation of the reaction rate and the particle size indicates that the infl uence of aragonite and vaterite is not crucial for the initial reaction rate.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It can be assumed that small particles completely reacted at this time and the size of the large particles is decisive. On the other hand, there is only a slight correlation between the reaction rate and the specifi c surface area of the samples, which is in accordance with the published data (Ahlbeck et al, 1993;Ahlbeck et al, 1995;Ukawa et al, 1993;Wallin and Bjerle, 1989;Dragan and Ozunu, 2012;Claudio A. Carleti G., 2015). Good correlation of the reaction rate and the particle size indicates that the infl uence of aragonite and vaterite is not crucial for the initial reaction rate.…”
Section: Resultssupporting
confidence: 91%
“…Calcium carbonate precipitated during the reaction of gypsum with CO 2 and ammonia may show different reactivity, mainly due to the different crystallographic modifi cation of calcium carbonate. A comparison of the reactivity and properties of limestone and calcium carbonate precipitate consisting of calcite was presented by Dragan and Ozunu (2012). Reactivity strongly depends on the particle size, the difference between the limestone and calcium carbonate precipitate was negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Several different flue gas desulfurization (FGD) technologies have been developed for this aim. This is the main reason why the issue of flue-gas desulfurization has become very topical and is the theme of numerous researches in this field [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A great prospect is the SO 2 absorption process into dolomite suspension thus reducing the amount of gypsum due to the fact that part of the sulfur is recovered as MgSO 4 , compound with many practical uses [9].…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic study of the SO 2 chemisorption process into dolomitebrucite suspensions revealed that the global process takes place according to the shrinking core model without crust or according to the unreacted core model with crust formation of the reaction products [9][10]. In the temperature range T = 293-333K and the suspension concentration C = 5-15% limitative steps of the global absorption process are the diffusional processes.…”
Section: Introductionmentioning
confidence: 99%